The Indeterminacy of the Risk Factor Prevention Paradigm: A Case Study of Community Partnerships Implementing Youth and Gang Violence Prevention Policy. (April 2014) - Goddard, Tim
In addition to methodological criticisms of the Risk Factor Prevention Paradigm (RFPP), numerous scholars have revealed that youth justice that is based on it reinforces the criminalization and exclusion of the most vulnerable and poorest youth in society. This article provides insight into the interpretation of the RFPP in local youth and gang violence prevention policy and practice. It uncovers that the RFPP is differentially conceptualized and articulated, such that some risk factors may be erased, others may be reinterpreted, and yet others may be raised to positions of prominence. I conclude that the RFPP is malleable and, thus, indeterminate.